2018
DOI: 10.1016/j.biomaterials.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD14 on blood derived cells improves intracortical microelectrode performance

Abstract: Intracortical microelectrodes afford researchers an effective tool to precisely monitor neural spiking activity. Additionally, intracortical microelectrodes have the ability to return function to individuals with paralysis as part of a brain computer interface. Unfortunately, the neural signals recorded by these electrodes degrade over time. Many strategies which target the biological and/or materials mediating failure modes of this decline of function are currently under investigation. The goal of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 57 publications
1
64
0
Order By: Relevance
“…Our analysis of the histological markers used in the current study demonstrated that there were significantly fewer neurons ( Figure 2 A) within the first 50 µm of the electrode site, compared to all further distances up to 400 µm. These results are consistent with previous reports from many labs, including our own [ 29 , 31 , 42 , 53 , 54 , 55 , 56 , 57 ]. Additionally, there was significantly more activated microglia/macrophages ( Figure 2 B), reactive astrocytes ( Figure 2 C), and blood–brain barrier permeability ( Figure 2 D) within the first 50 µm of the electrode site compared to further distances.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Our analysis of the histological markers used in the current study demonstrated that there were significantly fewer neurons ( Figure 2 A) within the first 50 µm of the electrode site, compared to all further distances up to 400 µm. These results are consistent with previous reports from many labs, including our own [ 29 , 31 , 42 , 53 , 54 , 55 , 56 , 57 ]. Additionally, there was significantly more activated microglia/macrophages ( Figure 2 B), reactive astrocytes ( Figure 2 C), and blood–brain barrier permeability ( Figure 2 D) within the first 50 µm of the electrode site compared to further distances.…”
Section: Resultssupporting
confidence: 94%
“…All channels were recorded continuously at 24,414 Hz for 10 min for later offline analysis. In the offline analysis, the relative size of the recorded action potentials for each isolatable unit was assessed for each electrode contact based on established methods [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…But for chronic implants, the body’s response at the tissue-microelectrode interface eventually leads to mechanical failure and signal degradation [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Despite extensive investigations into the inflammatory response and numerous trials investigating strategies to mitigate it, clearing this hurdle has remained elusive [ 5 , 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. It is consequentially one of the most important obstacles to overcome in order for neural interface technology to be fully realized.…”
Section: Tissue Reaction and Histopathologic Observations Due To Ementioning
confidence: 99%
“…Despite these numerous success stories, many challenges, and as a result, great opportunities remain unexplored [ 36 , 58 , 68 ]. There remains large variability in performance even between identical devices [ 69 ] due to both biological [ 58 , 67 , 70 , 71 , 72 ] and material integrity variance [ 73 , 74 , 75 ], even within the same subject [ 71 , 72 ]. Nevertheless, the field of neural engineering has reached a tipping point due to pioneers in neuroscience, technology development, and neurosurgery.…”
Section: Challenges On the Horizonmentioning
confidence: 99%